What Drives Task Performance in Fluency Tasks in People With HIV? - Rofes, Adrià; Sampedro, Bárbara; Abusamra, Lorena; Cañataro, Paola; Jonkers, Roel; Abusamra, Valeria (Frontiers in Psychology, 2021)
Introduction: Fluency tasks require language (i.e., semantics, phonological output lexicon, and phonological assembly) and executive functions (i.e., inhibition; mental set shifting; updating, and monitoring). Little is known about whether people with human immunodeficiency virus (HIV) are more impaired on a specific type of fluency task and what aspects of language and executive functions drive such performance. Aims: To understand (1) whether people with HIV are more impaired in animal, letter, or unconstrained fluency relative to a normative sample; (2) whether there exist differences between tasks relative to the total number of words; and (3) which aspects of executive function and language are involved in their performance. Methods: Data from animal, letter, and unconstrained fluency of 50 Spanish-speaking people with HIV were analyzed. The number of switches and mean cluster size for each task and 10 word properties (e.g., frequency, age of acquisition, length in graphemes) for each of the correct words were measured. A chi-square test was used to address Aim 1, linear mixed effects models for Aim 2, and random forests and conditional inference trees for Aim 3. The results were cross-validated with a normative sample. Results: People with HIV were not more impaired in animal, letter, or unconstrained fluency relative to a normative sample. People with HIV produced fewer words in letter fluency compared to animal and unconstrained fluency. In addition, they produced fewer words in animal fluency compared to unconstrained fluency. Number of switches emerged as the most important variable to predict the total number of correct words when considering the three tasks together and for each task separately. Word frequency was relevant to predict animal fluency, age of acquisition to predict letter fluency, and cluster size to predict unconstrained fluency. These results were cross-validated with the exception cluster size. Conclusion: People with HIV rely on language (phonological output lexicon, not necessarily semantics) and executive functioning (updating and monitoring) to produce words in fluency tasks. These results concur with the current literature. Future work may correlate fluency scores with other tests measuring language and executive functions or study other types of fluency tasks (e.g., action, cities, supermarket, and professions).